2022
DOI: 10.3390/ijms23073603
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(II) Coordination Polymers Supported by Bis-pyridyl-bis-amide and Angular Dicarboxylate Ligands: Role of Ligand Flexibility in Iodine Adsorption

Abstract: Reactions of N‚N’-bis(3-pyridylmethyl)oxalamide (L1), N‚N’-bis(4-pyridylmethyl)oxalamide (L2), or N,N’-bis(3-pyridylmethyl)adipoamide) (L3) with angular dicarboxylic acids and Ni(II) salts under hydro(solvo)thermal conditions afforded a series of coordination polymers: {[Ni(L1)(OBA)(H2O)]·H2O}n (H2OBA = 4,4-oxydibenzoic acid), 1, {[Ni(L1)(SDA)(H2O)2]·H2O·CH3OH}n (H2SDA = 4,4-sulfonyldibenzoic acid), 2, {[Ni(L2)(OBA)]·C2H5OH}n, 3, {[Ni(L2)(OBA)]·CH3OH}n, 4, {[Ni2(L2)(SDA)2(H2O)3]·5H2O}n, 5, {[Ni2(L2)(SDA)2(H2O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…By fixing the similar factors, we have shown that the best adsorption factor of 290.0 mg g −1 at 60 °C for 360 min was observed for 5 , demonstrating the important role of the flexibility of the neutral spacer ligands, L 1 , L 2 and L 3 , in determining the iodine adsorption capacities of 1 – 6 . For comparison, it is noted that the interpenetrated Th-SINAP-16 and Th-SINAP-21 appear to exhibit uptake amounts of 354 and 375 mg g −1 , respectively, after 0.5 h of iodine adsorption [ 21 ], whereas the Ni(II) CP {[Ni( L 3 )(OBA)(H 2 O) 2 ]·2H 2 O} n encapsulates 166.55 mg g −1 iodine at 60 °C [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By fixing the similar factors, we have shown that the best adsorption factor of 290.0 mg g −1 at 60 °C for 360 min was observed for 5 , demonstrating the important role of the flexibility of the neutral spacer ligands, L 1 , L 2 and L 3 , in determining the iodine adsorption capacities of 1 – 6 . For comparison, it is noted that the interpenetrated Th-SINAP-16 and Th-SINAP-21 appear to exhibit uptake amounts of 354 and 375 mg g −1 , respectively, after 0.5 h of iodine adsorption [ 21 ], whereas the Ni(II) CP {[Ni( L 3 )(OBA)(H 2 O) 2 ]·2H 2 O} n encapsulates 166.55 mg g −1 iodine at 60 °C [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ability of the CPs to adapt iodine molecules to the voids of the network structures may govern the iodine adsorption capacity [16][17][18][19]. The solvent accessible volumes calculated by using the PLATON program [20] for 1-6 were 1.5, 17.3, 34.4, 2.9, 11.8 and 10.4%, respectively, of the unit cell volume, indicating that complex 3, which displays the three-fold interpenetrated 3D net with (4 12 •6 3 )-pcu topology, may accommodate more iodine than the other complexes.…”
Section: Iodine Adsorptionmentioning
confidence: 99%
“…The ligands N ‚ N′ -bis(3-pyrid-yl-methyl)oxalamide ( L 1 ) and N ‚ N′ -bis(4-pyrid-yl-methyl)oxalamide ( L 2 ) were prepared according to a published procedure with some modification. 15…”
Section: Methodsmentioning
confidence: 99%
“…The ability of the CPs to adapt iodine molecules to the voids of the network structures may govern the iodine adsorption capacity [18][19][20][21]. The solvent accessible volumes calculated by using the PLATON program [22] for 1 -6 were 1.5, 17.3, 34.4, 2.9, 11.8 and 10.4 %, respectively, of the unit cell volume, indicating that complex 3 that displays the 3-fold interpenetrated 3D net with the (4 12 6 3 )pcu topology may accommodate more iodine than the other complexes.…”
Section: Iodine Adsorptionmentioning
confidence: 99%